On the Existence of Perfect Linear Codes Over Z2′ with Respect to Homogenous Metric - Siap, Irfan; Ozen, Mehmet; Siap, Vedat (SPRINGER HEIDELBERG, 2013)
In this paper, we obtain bounds for error correcting codes of some particular homogeneous weights over the ring of integers modulo . We also study these bounds to check for perfect linear codes and have shown the non-existence of one error correcting perfect codes with respect to the homogeneous weight.
Keywords: Codes over Z(2l); Homogenous weights; Perfect codes; NONEXISTENCE; Science & Technology - Other Topics